Implicaciones del Comercio Informal en el contexto del modelo de Desarrollo Local en la ciudad de Riobamba. - Salazar Zúñiga, María Cumandá (2023)
ABSTRACT: The present investigative work, which is entitled "Implications of informal trade in the context of the local development model in the city of Riobamba", is specifically based on knowing the probable consequences that informal trade has brought for a correct development for the Riobamba city; As we have been able to observe at present, informal commerce is a phenomenon that is gaining more and more a place within the economy of most countries, Ecuador is no exception, even more so in our city, since informal commerce has been increasingly increasing, the same that causes disorder and discomfort in many citizens. Local development is not just a job that corresponds to a certain institution, what must be had is a development model, where the participation of the authorities and citizens is incorporated, who demonstrate the resources and potentials that their territory has. , that way you can build your own development. In the field work that was carried out for the present investigation, it was possible to appreciate the condition of informal workers, the contempt they suffer from formal vendors, the municipal police or consumers, in the same way the unhealthy way the that offer food for consumption, this makes them become undignified work for each informal trader looking for a way to survive. Interviews were also conducted with the competent authorities on this issue of the Municipal Decentralized Autonomous Government of the Riobamba Canton, the same ones that mostly agreed to say that informal commerce is a latent problem in our city, a definitive solution has not been sought where the informal traders can formalize their work. With the investigation carried out, a proposal for an ordinance is presented for the control and adequate development of the commercial activities of the self-employed workers of the Canton Riobamba, the same one that aims to control and regulate the commercial activities of the self-employed workers for an adequate development of the same, on the outskirts of the markets and in the center of the Riobamba Canton.